Mind Mapping Learning Model To Improve Learning Outcomes About Solving Problems In Mathematics Subjects - Munib, Abdul (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
Observations in Class VI of SD Negeri 3 Blingoh show that mathematics learning for Semester 1 of the 2021/2022 academic year needs to be improved in order to increase students' ability to solve problems. To improve the quality of education and increase the ability to solve problems, there is a need for reforms in the field of education, including learning models. One of the mathematics learning models offered to improve the quality of education is mind mapping. By using the mind mapping learning model, it can be used as an alternative model in mathematics learning activities. In cycle II, students have shown encouraging learning results, namely that out of 19 students, 18 students or 95% have mastered the material and 1 student or 5% have not reached the completion standard. The implementation of cycle II learning improvements has reached the standard of completeness.